Understanding the Economic and Financial Impacts of Natural Disasters - Benson, Charlotte (Washington, DC: World Bank, 2013)
The study described here examines the short- and long-term economic, and financial impacts of natural disasters. It relies in part, on in-depth case studies of overall sensitivity to natural hazards in the small island economy of Dominica; public finance consequences of disasters in Bangladesh; and, the economic consequences of climatic variability, and the use of climatic forecasting in Malawi and southern Africa. Policy implications are drawn, and, where appropriate, recommendations are made. Finally, directions for future research, and cooperation are outlined. Major natural disasters can, and do have severe negativeshort-run economic impacts, and also appear to have adverse longer-term consequences for economic growth, development, and poverty reduction. But negative impacts are not inevitable. A full reassessment of the economic, and financial impacts of a major disaster, should be made 18 to 24 months after the event. It should be taken into account in reviewing the affected country's short-term economic performance, and the assistance strategy for the country. Vulnerability to natural hazards is determined by a complex, dynamic set of influences that include the country's economic structure, stage of development, and prevailing economic and policy conditions. The eclectic approach adopted in this study, which employed largely qualitative methods, is particularly useful in exploring the many complex, and dynamic pathways through which extreme hazard events influence an economy, and its financial system, as well as for identifying areas, and issues where further investigation, including quantification, would be worthwhile.